Direct CP violation searches in charmless hadronic B meson decays - Aubert, B; Boutigny, D; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Robbe, P; Tisserand, V; Palano, A; Pompili, A; Chen, G; Chen, J; et al. (2002)
We search for direct CP violation in charmless hadronic B decays observed in a sample of about 22.7 million B B̄ pairs collected with the BABAR detector at the SLAC PEP-II asymmetric-energy e+e- collider. We measure the following charge asymmetries: ACp(B ±→η′K±=-0.11±0. 11±0.02, ACP(B±→ωπ ±) = -0.01 -0.31+0.29±0.03, ACPB±→φK±)= -0.05±0.20±0.03, ACP(B± → φK*±)= -0.430.30+0.36±0.06, and ACP(B0→φ K*0)=0.00±0.27±0.03. © 2002 The American Physical Society.